Parotocinclus seridoensis, a new hypoptopomatine catfish (Siluriformes: Loricariidae) from the upper rio Piranhas-Açu basin, northeastern Brazil - Ramos,Telton Pedro A. (2013)
A new species of Parotocinclus is described from the upper rio Piranhas-Açu basin, northeastern Brazil. The new species differs from all its congeners, except P. bidentatus, P. muriaensis (both from rio Paraíba do Sul basin, southeastern Brazil), and P. spilurus (rio Jaguaribe basin, northeastern Brazil) by presenting the adipose fin rudimentary or absent. The new species differs from P. bidentatus, P. muriaensis, and P. spilurus mainly by presenting the abdomen region extensively naked, with few reduced rounded dermal platelets between the pectoral girdle and the anus. Parotocinclus seridoensis is probably an endemic species of the semi-arid Caatinga, region where the genus presents high species richness.